Alkaline rocks and carbonatites of the world. Part 4, - Woolley, A. R. (The Geological Society of London, 2019)
Although the great diversity of alkaline rocks, with their relatively exotic mineralogies, has always attracted the interest of petrologists, as have the relatively recently defined carbonatites, it could be argued that little progress has been made over the past 50 years towards formulating a comprehensive petrogenesis of these rocks. It could also be maintained that as the alkaline varieties have the most extreme compositions of all igneous rocks, so an understanding of their genesis is essential if we are to understand fully the workings of the solid Earth, whilst a knowledge of the most extreme products of differentiation must inevitably cast light on rocks of less extreme composition.